Synthesis of new 7‐amino‐3, 4‐dihydroquinolin‐2(1H)‐one‐peptide derivatives and their carbonic anhydrase enzyme inhibition, antioxidant, and cytotoxic activities. Issue 11 (27th July 2021) - Küçükbay, Hasan; Gönül, Zeynep; Küçükbay, Fatümetüzzehra Zehra; Tekin, Zehra; Angeli, Andrea; Bartolucci, Gianluca; Supuran, Claudiu T.; Tatlıcı, Eray; Apohan, Elif; Yeşilada, Özfer
Abstract: Six new monopeptides, seven new dipeptides, and two deprotected monopeptide dihydroquinolinone conjugates were prepared by the benzothiazole‐mediated method and their structures were confirmed by nuclear magnetic resonance, mass, infrared spectroscopy, and elemental analysis methods. The human carbonic anhydrase (hCA) I and hCA II enzyme inhibition activities of the compounds were determined using the stopped‐flow instrument. The synthesized peptide–dihydroquinolinone conjugates 2, 3, 6, 10, 13, and 15 showed inhibition against the hCA II enzyme in the range of 15.7–65.7 µM. However, none of the compounds showed inhibition of hCA I at a concentration of 100 µM. The antioxidant activities of the compounds were also examined using the DPPH (2, 2‐diphenyl‐1‐picrylhydrazyl) radical scavenging method at concentrations of 12.5–125 µg/ml, but when compared with the standard antioxidant compounds α‐tocopherol and butylated hydroxyanisole (BHA), weak antioxidant activities were detected. The cytotoxic effects of four compounds against the A549 and BEAS‐2B cell lines were also investigated. Among the compounds studied, compound 7 was found to be most effective, with the IC50 values on the A549 cells for 48 and 72 h being 26.87 and 9.979 µg/ml, respectively, and the IC50 values on the BEAS‐2B cells being >100 µg/ml. None of the tested compounds showed antimicrobial activity in the concentration range (800–1.56 µg/ml) studied. Abstract : New monopeptide, dipeptide, and deprotected monopeptide dihydroquinolinone conjugates were synthesized and tested for their inhibitory activities on human carbonic anhydrase (hCA) I and hCA II. Peptide–dihydroquinolinone conjugates 2, 3, 6, 10, 13, and 15 showed inhibition of hCA II at 15.7–65.7 µM, but none of the compounds showed inhibition of hCA I at 100 µM. Compound 7 was found to be most cytotoxic for A549 and BEAS‐2B cells.